VITAMIN D DEFICIENCY IN PAKISTAN: TIP OF ICEBERG - Jadoon, Shakeel Ahmed; Ahmed, Ashfaq; Alam, Muhammad Adeel (Journal of Ayub Medical College Abbottabad, 2017)
Abstract: Background: Vitamin D deficiency is becoming a public health problem and involves every segment of the population irrespective of age and gender. This study was conducted to assess its status in patients presenting with generalized body aches and pains. Methods: This cross-sectional study was conducted at Ayub Teaching Hospital Abbottabad from March 2015 to October 2016. A sample of 202 patients presenting with generalized body aches and pains were enrolled for the study using convenient sampling technique. Blood samples were taken and serum vitamin D levels were measured. The data was analysed using SPSS version 16. Results: There were 165 (81.7%) women and 37 (18.3%) men. The mean age was 42.39±15.89 years. The mean serum vitamin D level was 25.15±18.97 ng/ml with a minimum and maximum value of 9.60 ng/ml and 98.0 ng/ml respectively. Deficient serum vitamin D levels (<20 ng/ml) was found in 128 (63.4%) patients, 30 (14.9%) patients showed insufficiency (20 to 30 ng/ml) while only 44 (21.8%) had normal levels (>30 ng/ml). There was no statistically significant difference in the levels of the vitamin D deficiency with respect to gender and age groups. Conclusion: Vitamin D deficiency is affecting the Pakistani population irrespective of age and gender, and the results of this study have demonstrated that vitamin D deficiency in Pakistan is the tip of iceberg. Keywords: Vitamin D deficiency, Insufficiency, Musculoskeletal disorders, Rickets, Osteoporosis